STUDI EKSPERIMENTAL PEMISAHAN MINYAK-AIR MENGGUNAKAN HIDROSIKLON-BUBBLE GENERATOR - Catrawedarma; Sari, Eli Novita; Fiveriati, Anggra; Wahid, Muhammad Abdul; Pamuji, Dian Ridlo; Syaifuddin, Muhammad (POLITALA PRESS, 2024)
This research aims to analyze the performance of oil-water separation using a hydrocyclone-bubble generator. The bubble generator used was an ejector type to make it easier to suck in atmospheric air. The research was carried out by injecting an oil-water mixture through a bubble generator before entering the hydrocyclone system. The air flow injected into the bubble generator was varied from 0.1-1.5 lpm. From experimental studies, it was found that as the air flow increased, the split ratio also increased. The pressure drop at the overflow increases gently while the underflow pressure drop increases significantly along with increasing input air flow. The greater the input air flow, the more significant the difference in underflow and overflow pressure drop. It has implications for a larger pressure drop ratio. The greater the air flow, the greater the overflow efficiency decreases, and the underflow efficiency increases. The highest efficiency in overflow is 87.77%.